Pengaruh Literasi Keuangan Dan Persepsi Risiko Terhadap Minat Berinvestasi (Studi Kasus Mahasiswa Universitas Muhadi Setiabudi Angkatan 2020) - Dhita Putri Aprilia; M. Badrun Zaman; Yenny Ernitawati (JURNAL ILMIAH NUSANTARA, 2024)
. This study looks at how risk perception and financial knowledge affect students at Muhadi Setiabudi University's Brebes Classof 2020's interest in investing. Themet hodused is the applied causal quantitative method. Primary data is what is used. The distribution of questionnaires is the main technique used to collect data. Purposive sampling was the method employed, and the sample size consisted of 76 respondents. Multiple linear regression analysis, classical assumption testing, and instrument testing were used to conduct the tests. Thefindings of this research based onthet test, among other things, demonstrate the beneficial impact of financial literacy on students' interest in investing. This is shown by the significance value of 0.001 < 0.05 and the projected t score of 9.842 > the Table t value of 1.993. Students' perception of risk has a beneficial effect on their interest in investing. This is shown by the significance value of 0.001 <\0.05 and the projected t value of 9.288 > t table value of 1.993. Based on the test findings, which indicated that the determined f value was 55.701 as the f table value was 3.12, it is clear that the determined f value > f table with a significance level of 0.000 < 0.05. Consequently, When financial literacy and risk perception are present at the same time, it favorably affects students' interest in investing